Analisis Pembangunan Olahraga Kecamatan Bojonegoro Kabupaten Bojonegoro Ditinjau Dari Sport Development Index - Muhammad Maulana Yossyan Fachrozi; Achmad Widodo (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
The impact of the pandemic has changed the daily lives of the people of Bojonegoro District, especially sports activities, which have become completely paralyzed, so that sports facilities and infrastructure are not utilized properly. This research aims to determine the availability of open sports space, the level of community participation in sports, and the level of community physical fitness after the COVID-19 pandemic through analysis of the Sport Development Index (SDI). The research method used is quantitative descriptive with Stratified Random Sampling and Cluster Sampling sampling techniques. The sample consisted of 30 people representing three age groups: 10-19 years, 20-44 years, and 45-60 years. The results of the research show that the level of open sports space is in the middle category, with the Bojonegoro sub-district open space index being 0.54, while the level of community participation and physical fitness is in the low category according to SDI with the Bojonegoro sub-district sports participation index being 0.333 and the physical fitness index value Bojonegoro sub-district is 0.1837. The researcher's suggestion is that the Bojonegoro Youth and Sports Department (Dinpora) pay more attention to sports development in Bojonegoro District to increase the level of participation and physical fitness of the community after the pandemic.